Brand Attachment Vs. Brand Love: To What Extent Are They Identical? - Martiyanti, Dwi; Dharmmesta, Basu Swastha; Nugroho, Sahid Susilo; Aritejo, Bayu Aji (JDM (Jurnal Dinamika Manajemen), 2021)
Brand attachment and brand love is important marketing concepts in developing a strong relation- ship of brand. Nevertheless, up to now the boundaries of these two concepts are still blurred. This research seeks to study the two constructs of brand attachment and brand love at the conceptual, definition and operational dimensions. The study was carried out by in-depth examination of articles related to brand attachment and brand love. Each of these constructs is defined and presented in rela- tion to theoretical concepts, operational dimension and measurement patterns that have been used in empirical research. In the end, this review reveals that although there are similarities between brand attachment and brand love, they are different. This difference is viewed from the concepts, measure- ment dimension and intensity between the two. Brand attachment and brand love are two constructs that have emotional content and influence the behavior to maintain the relationship with a brand. However, band attachment is “more self- focused” relative to the thoughts and feelings of a particular object; whereas brand love is “more brand-focused” which includes cognitive consistency, power of great positive attitude, more frequent thoughts and conversations about the object of attitude.